Girjas Reindeer Herding Community v. Sweden: Analysing the Merits of the Girjas Case - Allard, Christina; Brännström, Malin (Arctic Review on Law and Politics, 2021)
For the first time in the Swedish Supreme Court, a small Sami reindeer herding community has won an important victory affirming the community’s small game hunting and fishing rights. Because of protracted use and the concept of immemorial prescription, the Court recognised the community’s exclusive hunting and fishing rights, including the right to lease these rights to others. Such leases have long been prohibited by legislation and the State has retained its powers to administer such leases. This case signifies a considerable development in the area of Sami law. In its decision, the Supreme Court made some adjustments to the age-old doctrine of immemorial prescription, and provided insights into how historic evidence should be evaluated when the claimant is an Indigenous people. A common motivator for these adjustments is an enhanced awareness of international standards protecting Indigenous peoples and minorities. Even ILO Convention No.169 – the only legally binding convention concerning Indigenous rights, but which Sweden has not yet ratified – is relevant when it comes to evaluating Sami customary uses. The Court addressed the problem of gaps in the historical material and used evidence from other parts of Swedish Lapland and adjacent time-periods, making reasonable assumptions to fill in these gaps. The Court imposes on the State the burden of proof regarding the extinguishment of already established Sami rights, as well as proof that extinguishment by legislation or expropriation, is “clear and definitive”. These conditions were not met in this case.